2013
DOI: 10.1021/jp312391h
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Induced Shape Evolution of FeNi Nanoalloys and Their Air Stability by in-Situ Surface Passivation

Abstract: Shape and size of nanoparticles are fundamental structural properties that govern the development of novel surface-related applications. Traditionally external agents such as surfactants, reducing agents, or stabilizers have been used for enforcing preferential growth orientation, size, and shape to develop tailor-made nanoparticles. However, these external agents cover the pristine surface of the particle and invariably reduce the surface activity. Here, we introduce a surfactant-free, single-step electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This confirmed that the interaction between Fe and Ni resulted in a structural variation of active sites, leading to significant differences in the reaction mechanism and product selectivity. was calculated to be 3.575 and 3.570 Å, respectively, which is slightly larger than that of metallic Ni, indicating the formation of Ni-rich NiFe alloy with fcc structure (22). This conclusion was verified by the corresponding peak shift for both catalysts under various treatment conditions ( Fig.…”
Section: Significancesupporting
confidence: 55%
“…This confirmed that the interaction between Fe and Ni resulted in a structural variation of active sites, leading to significant differences in the reaction mechanism and product selectivity. was calculated to be 3.575 and 3.570 Å, respectively, which is slightly larger than that of metallic Ni, indicating the formation of Ni-rich NiFe alloy with fcc structure (22). This conclusion was verified by the corresponding peak shift for both catalysts under various treatment conditions ( Fig.…”
Section: Significancesupporting
confidence: 55%
“…The peaks at 855.7 and 861.5 eV are from surface oxidized Ni 2+ [35,36]. Further analysis reveals a positive binding energy shift for Ni 2p3/2 in comparison with reported FeNi system [38,39]. Figure 3(d) shows the metallic Fe with binding energy at 706.8 eV, and the fitted signals at 707.9, 710, 711.3, 712.5, and 713.5 eV are surface oxidized Fe 2+ [35,40].…”
Section: Resultsmentioning
confidence: 55%
“…Figure 3(d) shows the metallic Fe with binding energy at 706.8 eV, and the fitted signals at 707.9, 710, 711.3, 712.5, and 713.5 eV are surface oxidized Fe 2+ [35,40]. Moreover, a slight positive shift is on Fe 2p3/2 compared to pure FeNi system [38,39]. Therefore, the variation of electronic structure results in the interfacial interaction between FeNi NPs and Mo2TiC2Tx, which can effectively affect the electrocatalytic activity.…”
Section: Resultsmentioning
confidence: 97%
“…The doublets at 853.1 eV/870.7 eV and 707.3 eV/720.8 eV are ascribed to Ni 0 and Fe 0 accordingly, representing the metallic Ni and Fe in the alloy. The peaks located at 854.9 eV, 856.7 eV and 711.7 eV are assigned to Ni 2+ , Ni 3+ and Fe 3+ , respectively, all of which result from the in‐situ oxides formed at the exposed alloy surfaces . As the XRD and Raman analyses did not depict crystalline oxide phases, it is possible that these surface oxides are either clusters or amorphous in nature.…”
Section: Figurementioning
confidence: 99%